If the Asian green mussel, Perna viridis (Linnaeus, 1758), poses the greatest invasive marine species threat to Australia, why has it not invaded? - Wells, Fred (CSIRO Publishing, 2017)
© 2017 The Malacological Society of Australasia and the Society for the Study of Molluscan Diversity. A national approach has been developed to the problem of invasive marine species (IMS) in the Australian marine environment. Fifty-five species were listed as posing significant threats to Australia. A 2005 analysis of the scientific literature concluded that the Asian green mussel Perna viridis (Linnaeus, 1758) poses the greatest threat to Australia. The mussel has in fact successfully invaded many areas of the world’s oceans. Despite the numerous and varied opportunities for P. viridis to be distributed to northern Australia it has not established a known population on the continent, perhaps suggesting there are biological factors inhibiting its establishment. The invasion success of P. viridis in many parts of the world and its failure so far to establish in Australia make the species ideal for testing theories of the factors determining invasion success. Such research will allow a reconsideration of the invasion threat the species poses to the Australian marine environment.